2021
DOI: 10.3390/molecules26082159
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Carbons of Well-Organized Structure in the Removal of Dyes from Aqueous Solutions

Abstract: Mesoporous carbons with differentiated properties were synthesized by using the method of impregnation of mesoporous well-organized silicas. The obtained carbonaceous materials and microporous activated carbon were investigated by applying different methods in order to determine their structural, surface and adsorption properties towards selected dyes from aqueous solutions. In order to verify applicability of adsorbents for removing dyes the equilibrium and kinetic experimental data were measured and analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…Although CAC is exceptionally efficient at removing MB dye, its high cost is a significant barrier for largescale applications, particularly in industries. It has been demonstrated that a high percentage of cellulose and AC significantly impact the uptake of dye molecules, similar to the findings reported by other authors (Blachnio et al 2021). The porous structure and large surface area of activated carbon provide the sample with numerous vacant sites for the adsorption of dye molecules to take place.…”
Section: Evaluation Of the Dye Adsorption Performance Of The Mixturessupporting
confidence: 86%
See 1 more Smart Citation
“…Although CAC is exceptionally efficient at removing MB dye, its high cost is a significant barrier for largescale applications, particularly in industries. It has been demonstrated that a high percentage of cellulose and AC significantly impact the uptake of dye molecules, similar to the findings reported by other authors (Blachnio et al 2021). The porous structure and large surface area of activated carbon provide the sample with numerous vacant sites for the adsorption of dye molecules to take place.…”
Section: Evaluation Of the Dye Adsorption Performance Of The Mixturessupporting
confidence: 86%
“…The mesoporous structure has a relatively large surface area, including a high pore volume making the sample suitable for dye removal (Blachnio et al 2021). The generated curves represent the characteristics of the pores and their sizes in which the SEM could not carry out the identification (Phothong et al 2021).…”
Section: Bet Analysismentioning
confidence: 99%
“…Taking into account the complex porous structure formed during carbon preparation (especially during the removal of the silica matrix when the extended porosity is formed), it is possible to obtain a hierarchical porous structure with elements of similar sizes. This can be confirmed by TEM images, which show extensive porosity with such characteristics [ 60 ]. Taking into account the course of the scattering curve, carbon materials differentiate into two groups.…”
Section: Resultsmentioning
confidence: 79%
“…The high affinity of carbons for methylene blue is frequently observed [ 60 , 69 , 70 , 71 ] and can be attributed to (i) strong attractive interactions between the deprotonated functional groups on the adsorbent surface and the ionized adsorbate; (ii) π–π interactions of the adsorbent graphene layers with the adsorbate aromatic polyring; (iii) free dispersion interactions (London forces); (iv) hydrogen bonds between nitrogen, sulphur, or hydrogen atoms (methyl groups) of the adsorbate molecule and hydrogen or oxygen atoms belonging to the adsorbent surface groups. In the case of polymers, their much lower affinity for methylene blue is due to (i) repulsive electrostatic forces between the weakly positively charged adsorbent particles and the adsorbate cation; (ii) lack of or slight interactions resulting from differences in the distribution of electron density in aromatic systems (X-ray diffraction studies).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation